Effectiveness and Safety of Endovascular Treatment in Large Vessel Occlusion Stroke with an NIHSS Score of ≤5 Exhibiting Predominant Cortical Signs - Chulho Kim; Seung Joon Oh; Jae Jun Lee; Jong-Hee Sohn; Joo Hye Sung; Yerim Kim; Minwoo Lee; Mi Sun Oh; Kyung-Ho Yu; Hee Jung Mo; Sang-Hwa Lee (Biomedicines, 2025)
Background: Our study aimed to evaluate the impact of EVT on stroke outcomes in patients with LVO with a National Institute of Health Stroke Scale (NIHSS) score of ≤5, exhibiting primarily cortical signs. Methods: We conducted a multicenter registry-based analysis of patients with acute ischemic stroke with LVO who arrived within 12 h of onset. Among these, patients with low NIHSS scores and prominent cortical signs (Items 2, 3, 9, or 11) were included. Patients were divided into two groups: those who underwent EVT and those treated with the best medical therapy (BMT), which included intravenous thrombolysis where appropriate. The primary outcome measure was a modified Rankin scale (mRS) score of 0–1 at 3 months and symptomatic hemorrhagic transformation (SHT). We performed logistic regression analysis to evaluate the impact of EVT on the outcomes. Results: Of the 970 patients with LVO, 291 met the inclusion criteria, with 95 and 196 undergoing EVT and BMT, respectively. The EVT group demonstrated a significantly higher rate of 3-month mRS score of 0–1 (65.3% vs. 39.3%, p < 0.001) and a lower incidence of SHT than the BMT group (3.2% vs. 12.8%, p = 0.01). Multivariate analysis confirmed that EVT was associated with improved functional recovery (mRS score, 0–1; odds ratio [OR], 3.61; 95% confidence interval [CI], 1.82–7.06; p < 0.001) and reduced risk of SHT (OR, 0.19; 95% CI, 0.05–0.74; p = 0.02). Notably, patients with specific cortical signs, such as aphasia and spatial neglect, exhibited better outcomes with EVT. Conclusions: EVT may significantly improve the functional outcomes in patients with mild LVO stroke who present with cortical signs, despite low NIHSS scores. These findings suggest that cortical signs should be a key factor in EVT decision-making for mild stroke cases, thereby advocating for a more individualized approach in acute stroke management.